Efektivitas Penggunaan Quizizz sebagai Media Penilaian Siswa pada Mata Pelajaran TIK - Dwi Karmila; Lita Wulandari; Ceryl Monica; Zikri Dawam Zulhimar; Agetha Elan Novia (Departement of Mathematics Education, 2023)
This study uses a quantitative descriptive analysis method. The research was conducted by teaching ICT material in two meetings, then at the end of the second meeting a learning evaluation was carried out. Evaluation of learning is done by giving questions about the material that has been taught. The subjects of this study were 23 students of class VIII SMPN 19 Pontianak. This research was conducted by giving questionnaires to students of SMP Negeri 19 Pontianak to collect data. Based on the questionnaire distributed to class X students of SMP Negeri 19 Pontianak, the following data were obtained based on 23 respondents who filled out the questionnaire/questionnaire survey and then processed it using a Likert scale calculation. Based on the statistics mentioned above, the majority of students answered positively or agreed with the evaluation of student motivation in Information and Communication Technology (ICT) subjects. Based on the summary of the 12 indicators questionnaire, it can be concluded that the use of Quizizz in class VIII SMP Negeri 19 Pontianak was successful with an average percentage of 94.17%.